Online auctions the Internet guide for bargain hunters and collectors - O'Loughlin, Luanne (McGraw-Hill, 2000)
The world's greatest sales are happening right now on the Web -- with 600,000 online auctions held every day at eBay. AOL. and thousands of other venues! Bidders and sellers alike will jump on this definitive guide to the newest e-market place, where the rules of shopping are being rewritten by technology. Three e- commerce mavens show how to master Web auction lingo, find the goods, avoid frauds, plunge into the action, check out the related classifieds, and save (or make) a bundle of money from the comfort of your own desktop.